EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI CABAI RAWIT DI KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR - Yusuf, Muhammad; Septiadi, Dudi (JURNAL AGRITA, 2024)
The research aims to: (1) Analyze production factors that influence the production of cayenne pepper farming in Sakra District, East Lombok Regency; (2) Analyzing the efficiency of using production factors in cayenne pepper farming in Sakra District, East Lombok Regency. The method used is a descriptive method, while data collection was carried out using survey techniques on a sample of 30 respondents. Data were analyzed descriptively quantitatively, using the Cobb-Douglas model regression function. The results of the research show that: (1) Production factors that have a positive influence on the production of cayenne pepper farming in Sakra District, East Lombok Regency include land area, seeds, urea fertilizer, NPK, and pesticides, meanwhile. Production factors that were declared to have no effect included the variables SP-36 fertilizer and labor; (2) The use of production factors (input) for cayenne pepper in Sakra District, East Lombok Regency, in the form of land area, Urea, NPK, SP-36, and pesticides is not yet efficient (its use is still insufficient), while the use of production factors in the form of seeds and labor is not efficient (excessive).